Engineering the synergistic effect of carbon dots‐stabilized atomic and subnanometric ruthenium as highly efficient electrocatalysts for robust hydrogen evolution. Issue 2 (29th September 2021) - Liu, Yuan; Chen, Ning; Li, Weidong; Sun, Mingzi; Wu, Tong; Huang, Bolong; Yong, Xue; Zhang, Qinghua; Gu, Lin; Song, Haoqiang; Bauer, Robert; Tse, John S.; et al.
Abstract: Currently, the most efficient electrocatalyst for the hydrogen evolution reaction (HER) in water dissociation is Pt‐based catalyst. Unfortunately, the high cost and less than perfect efficiency hinder wide‐range industrial/technological applications. Here, by controlling the treatment temperature of tris (2, 2‐bipyridine) ruthenium dichloride hexahydrate, synthesis of compounds with novel ruthenium single/dual atoms (Ru S/DAs) mixed with Ru nanoclusters (Ru S/DAs + Ru NCs) and supported by carbon dots is demonstrated. These compounds are shown to be highly efficient and competitive catalysts for hydrogen evolution. Ru S/DAs + Ru NCs exhibit very high activity, with overpotentials of 15 and 40 mV at a current density of 10 mA/cm 2 in 1.0 mol/L KOH and 0.5 mol/L H2 SO4, respectively. Furthermore, the composites are found to possess outstanding stability and rapid HER kinetics. X ray absorption fine structure analysis, supported by density functional theory calculations, shows charge rearrangement in single‐atomic Ru, and the Ru dual sites promote active hydrogen adsorption and recombination. Ru S/DAs and Ru NCs demonstrate high electroactivity due to the electroactive Ru 4d orbitals. The introduction of Ru NCs activates the carbon support, providing a high electronic conductivity to transfer electrons from Ru NCs to Ru S/DAs, and facilitates water dissociation for the HER process. Abstract : Atomic and subnanometric ruthenium anchored by carbon dots is demonstrated by controlling the treatment temperature of tris (2, 2‐bipyridine) ruthenium dichloride hexahydrate. These compounds are shown to be highly efficient and competitive catalysts for hydrogen evolution over a wide pH range.